2021
DOI: 10.1093/clinchem/hvab135
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Radioactivity in Patient Specimens Received in the Core Laboratory at a National Cancer Institute (NCI) Designated Cancer Center

Abstract: Background Biological specimens from patients who have received radiopharmaceuticals are often collected for diagnostic testing and sent to clinical laboratories. Residual radiation has long been assumed to be minimal. However, literature is sparse and may not represent the specimen volumes or spectrum of radionuclides currently seen at National Cancer Institute (NCI)–designated cancer centers. This study examined the radiopharmaceuticals associated with patient specimens received in the hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The study on the working status of the study subjects found that 53 cases (30.64%) were currently engaged in domestic work and 44 cases (25.43%) were still working, which was related to the fact that the survey subjects were mostly middle-aged women mainly from rural areas. The types of medical insurance of the survey respondents were mainly new rural cooperative medical insurance and urban employees, with 91 cases and 62 cases, accounting for 52.60% and 35.84%, respectively [ 8 , 21 , 22 ].…”
Section: Analysis Of Clinical Care Of Hyperthyroidism With Iot Wearab...mentioning
confidence: 99%
“…The study on the working status of the study subjects found that 53 cases (30.64%) were currently engaged in domestic work and 44 cases (25.43%) were still working, which was related to the fact that the survey subjects were mostly middle-aged women mainly from rural areas. The types of medical insurance of the survey respondents were mainly new rural cooperative medical insurance and urban employees, with 91 cases and 62 cases, accounting for 52.60% and 35.84%, respectively [ 8 , 21 , 22 ].…”
Section: Analysis Of Clinical Care Of Hyperthyroidism With Iot Wearab...mentioning
confidence: 99%
“…Due to the clearance of Lu‐177‐PSMA‐617, universal precautions are typically advised for three days post infusion. Universal precautions are also appropriate for medical lab personnel handling radioactive specimens and samples, if any 29 . For patients that have expired, NRC regulatory guide 8.39 revision 1 describes a general procedure for radioactive decedents (http://www.nrc.gov).…”
Section: Generate the Written Procedures And Accompanying Formsmentioning
confidence: 99%